Analysis of the development of the tourism and creative economy sector in Bima Regency, West Nusa Tenggara - Fanggidae, Rolland E.; Molidya, Aldarine; Guterres, Alexandre De Sousa (Journal of Multidisciplinary Academic Business Studies, 2024)
Purpose: This study aims to analyze the development of the tourism sector and the creative economy in the Bima district and the extent to which the tourism and creative economy sectors have contributed to economic growth at both the regional and national levels. Research Methodology: A descriptive qualitative approach was applied using SWOT analysis to identify internal strengths and weaknesses, as well as external opportunities and threats. Data were obtained through field observations, stakeholder interviews, and document reviews. Results: The analysis shows that Bima Regency possesses diverse tourism resources and creative economy products, but their development is uneven. Only destinations with large capital investments have progressed, while many potential attractions remain underdeveloped. Key weaknesses include limited certified tourism human resources, insufficient culinary training, low innovation among MSMEs, and weak collaboration. Conclusions: Tourism and creative economy development in Bima requires an aggressive S–O strategy that leverages strengths and opportunities by improving human resource capacity, enhancing MSME innovation, expanding culinary programs, and strengthening partnerships. Limitations: This study focused only on Bima Regency, limiting the generalizability of its findings to other regions. The qualitative nature of the research also restricts the quantitative measurement of economic impacts. Contribution: This study contributes to the regional development discourse by offering strategic insights for sustainable tourism and creative economy growth, aligning local initiatives with national policies to increase competitiveness and economic resilience.